种海水淡化方法和系统 (2017)
本发明提供种海水淡化方法和系统，所述方法先对需要淡化的原料液进行正渗透处理，原料液中的水从正渗透膜的低渗透压侧透过膜进入低渗透压侧的汲取液中；接着将所述汲取液加压后进行反渗透处理，在反渗透膜的低压侧得到脱盐的淡水；最后对脱盐的淡水进行膜蒸馏处理，水蒸汽透过膜，冷凝后得到纯化的淡水。相应地，海水淡化系统包括：原料液罐、汲取液罐、集水罐、正渗透膜组件、反渗透膜组件、膜蒸馏组件、蠕动泵、高压泵、加热器、冷凝器。本发明的方法和系统，能量消耗低，正渗透和膜蒸馏过程均不需要外加压力，对膜的污染较低，污染易于去除。 The invention provides a method and a system for sea water desalination. The method comprises the steps of firstly carrying out forward osmosis treatment on raw material liquid to be desalted, wherein water in the raw material liquid penetrates through a membrane and enters a draw solution at the low osmotic pressure side from the low osmotic pressure side of a forward osmosis membrane; pressurizing the draw solution, then carrying out reverse osmosis treatment so as to obtain desalted fresh water at the low pressure side of a reverse osmosis membrane; and finally carrying out membrane distillation treatment on the desalted fresh water, wherein the water vapor penetrates through the membrane and is condensed so as to obtain the purified fresh water. Correspond